Upaya Peningkatan Motivasi Belajar Lari Jarak Pendek melalui Metode Bermain pada Siswa Kelas V Sekolah Dasar - Suwarti, Titi (Universitas Sebelas Maret, 2018)
Abstract. Short distance learning in Mlese Gantiwarno Public Elementary School 2 in Klaten, which is monotonous, makes students feel bored so that the process and achievement of learning outcomes are less than optimal. This study aims to determine the increase in motivation to learn short distance running in fifth grade students of SD Negeri 2 Mlese Gantiwarno Klaten Semester II 2017/2018 Academic Year through the method of playing. This research is a Classroom Action Research. The subjects in this study were fifth grade students of SDN 2 Mlese, Gantiwarno District, Klaten Regency, which amounted to 20 students. Thedata collection technique uses observation sheets to determine student interest, motivation questionnaires, and student perform nce sheets. The results showed that the average score of the aspects of interest was 76.35 so that the average interest of students had exceeded 70, thus the interest of students had increased. The performance aspects of students showed an average value of 72.95, this indicates that the value of students has achieved a minimum of completeness, namely 70, so that the target of 70% of students completed has been fulfilled.Based on the motivation questionnaire shows that 64.1% of children have good motivation. The fifth grade students of SD Negeri 2 Mlese in each cycle experienced an increase and by giving the method of playing students felt happy or felt interested in taking short distance learning. So that learning through the method of playing approach in short distance running material in class V students of SD Negeri 2 Mlese has succeeded in increasing students' motivation and learning achievement in following the learning.